2009
DOI: 10.1055/s-0029-1210615
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Stimulated Adrenocortical Activity on the Concentration of Thyroxine and Triiodothyronine in Blood Serum of Piglets

Abstract: The effects of elevated adrenocortical activity, induced by cold exposure, weaning or starvation, or exogenous adrenocorticotrophin (ACTH) on the concentrations of thyroxine (T4) and triiodothyronine (T3) in blood serum were investigated in 99 sucking piglets and weaners, divided into five experiments. No changes in concentrations of circulating iodothyronines were recorded during a 3-hour exposure of 3- to 4-day-old piglets to ambient temperature of 8-12 degrees C. Two days after weaning of 4-week-old piglets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Therefore, calves were allowed continuous contact with their dams had lower stress on thyroid activity. Dvorak and Neumannova (1986) reported increased serum concentration of T 4 among piglets in response of weaning induced stimulated adrenocortical activity. They suggested that both specific stressor effects and circulating corticosteroids are responsible for the changes of T 3 and T 4 concentrations in blood sera of weaned animals.…”
Section: Thyroid Hormones Response:-mentioning
confidence: 95%
“…Therefore, calves were allowed continuous contact with their dams had lower stress on thyroid activity. Dvorak and Neumannova (1986) reported increased serum concentration of T 4 among piglets in response of weaning induced stimulated adrenocortical activity. They suggested that both specific stressor effects and circulating corticosteroids are responsible for the changes of T 3 and T 4 concentrations in blood sera of weaned animals.…”
Section: Thyroid Hormones Response:-mentioning
confidence: 95%